O texto literário na educação infantil: práticas e concepções de leitura dos professores na infância - Oliboni, Debora Gaspar Falkemback (2019)
Literature is of great importance for the social, emotional and cognitive development of the child, as well as for the promotion of competences and abilities that assist in the process of construction of the reading formation, and, therefore, many investigations are being done in this field. The book is an effective means in the first stage of Basic Education, one of the objects that contributes positively to the appropriation of reading in different forms, which contemplates both writing and image. This scientific research has as main objective to investigate the work carried out with the literature by the teachers of the Early Childhood Education of André Zaffari Municipal School, Passo Fundo/RS, in order to understand the reception and the interactions established in the moments of the reading experiences provided to the children. In addition, it is proposed to look at the education, conceptions and reading habits of these educators. In this line, literary reading is understood as an activity of a humanizing, emancipatory nature, as it frees the reader from its real world, taking it to a fictional dimension capable of transforming its reality. In this context, family mediation is also fundamental in the process of small-group literacy training. Through dialogue and interaction between the family and the school, it is possible to propose new ways of working with literature in Early Childhood Education, although this does not always happen. In this way, it is necessary to develop in children reading attitudes that make them autonomous, critical, and able to deal with challenges in a safe and efficient way. For this, a case study with a qualitative approach was adopted as methodological orientation, involving a detailed study on this specific subject, raising data through observations and questionnaires, being teachers and children the real subjects in concrete situations of teaching and learning. Based on the theoretical assumptions of Peter Hunt (2010), Elie Bajard (2014), Yolanda Reyes (2012), Tereza Colomer (2003), Regina Zilberman (2003), Michèle Petit (2013), Lúcia Pimentel Góes Junqueira (2016) and Cyntia Girotto (2018), the research revealed the need for teachers to invest in their training, especially in the area of children's literature, diversifying work, once it was shown that, despite being aware of the contributions and the importance of the literary text in the process of reading the child, some teachers insist on using a non-innovative methodology, without differentials. The importance and applicability of the reading of children's narratives as a promoter of various benefits in the scope of cognitive abilities, with an alert not to remain in the same practices, were evidenced in this investigation.